2010
DOI: 10.3324/haematol.2009.018267
|View full text |Cite
|
Sign up to set email alerts
|

Fludarabine, cyclophosphamide, antithymocyte globulin, with or without low dose total body irradiation, for alternative donor transplants, in acquired severe aplastic anemia: a retrospective study from the EBMT-SAA working party

Abstract: BackgroundWe analyzed the outcome of 100 patients with acquired severe aplastic anemia undergoing an alternative donor transplant, after immune suppressive therapy had failed. Design and MethodsAs a conditioning regimen, patients received either a combination of fludarabine, cyclophosphamide, and antithymocyte globulin (n=52, median age 13 years) or this combination with the addition of low dose (2 Gy) total body irradiation (n=48, median age 27 years). ResultsWith a median follow-up of 1665 and 765 days, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
156
1
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(167 citation statements)
references
References 19 publications
4
156
1
6
Order By: Relevance
“…Recently, Flu-based preconditioning regimen is widely used in HSCT for SAA from MSD or alternative donors. [14][15][16] In such situations, low-dose TBI is usually combined with chemotherapeutic agents to avoid rejection in Japan. Adverse effects of radiation include not only LM but also endocrinological disorders, such as hypothyroidism or hypogonadism, or other organ dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Flu-based preconditioning regimen is widely used in HSCT for SAA from MSD or alternative donors. [14][15][16] In such situations, low-dose TBI is usually combined with chemotherapeutic agents to avoid rejection in Japan. Adverse effects of radiation include not only LM but also endocrinological disorders, such as hypothyroidism or hypogonadism, or other organ dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclosporin A should be gradually reduced until it can be discontinued, in the absence of chronic GvHD, 6-12 months after HSCT. These later recommendations are derived from what has been published in acquired severe aplastic anemia from sibling donors 7 and unrelated transplantation, 8 using bone marrow as a stem cell source. Pre-transplantation serotherapy (either anti-thymoglobuline or alemtuzumab) is recommended for UD-HSCT, but not for matched sibling donor HSCT because of the associated immunosuppression in the early months post HSCT, which has the potential for higher transplantation-related morbidity and mortality owing to opportunistic infections.…”
Section: Gvhd Prophylaxismentioning
confidence: 99%
“…These findings suggested that sufficient hematopoietic recovery could be achieved without TBI in RIC allo-HSCT from an HLA-matched-related donor, as previously reported. 12,13 In contrast, Rodrigues et al reported that the addition of low-dose TBI to a RIC regimen improved neutrophil recovery and survival after cord blood transplantation. 7 Low-dose TBI may be important in the setting of unrelated donor transplantation.…”
mentioning
confidence: 99%